2015
DOI: 10.1371/journal.pone.0131080
|View full text |Cite|
|
Sign up to set email alerts
|

Biodiversity on the Rocks: Macrofauna Inhabiting Authigenic Carbonate at Costa Rica Methane Seeps

Abstract: Carbonate communities: The activity of anaerobic methane oxidizing microbes facilitates precipitation of vast quantities of authigenic carbonate at methane seeps. Here we demonstrate the significant role of carbonate rocks in promoting diversity by providing unique habitat and food resources for macrofaunal assemblages at seeps on the Costa Rica margin (400–1850 m). The attendant fauna is surprisingly similar to that in rocky intertidal shores, with numerous grazing gastropods (limpets and snails) as dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 1,878 publications
(69 citation statements)
references
References 72 publications
2
64
0
Order By: Relevance
“…At peripheries of seeps with lower influence from sulfide and methane, macrofaunal colonization of carbonates can be slower and more stochastic than at the center of the seep (Gaudron et al, 2010;Grupe, 2014). Sediment colonization experiments (Levin et al, 2006) and community surveys (Sahling et al, 2002;Levin et al, 2015) have also found that species composition of seep faunas tends to correspond to physicochemical conditions (sulfide, oxygen, substrate type), highlighting the importance of niche-based regulation of metacommunities.…”
Section: Seeps As a Contrast To Ventsmentioning
confidence: 98%
See 1 more Smart Citation
“…At peripheries of seeps with lower influence from sulfide and methane, macrofaunal colonization of carbonates can be slower and more stochastic than at the center of the seep (Gaudron et al, 2010;Grupe, 2014). Sediment colonization experiments (Levin et al, 2006) and community surveys (Sahling et al, 2002;Levin et al, 2015) have also found that species composition of seep faunas tends to correspond to physicochemical conditions (sulfide, oxygen, substrate type), highlighting the importance of niche-based regulation of metacommunities.…”
Section: Seeps As a Contrast To Ventsmentioning
confidence: 98%
“…Cold seeps typically occur in soft sediment settings, but carbonate precipitation associated with AOM eventually creates hard substrata, which contain their own unique faunal assemblage (Levin et al, 2015). In short-term (∼1 year) colonization and transplant experiments, carbonate assemblages of colonists responded strongly to geochemical heterogeneity and colonists resembled late successional assemblages on seep carbonates in Costa Rica and Oregon, suggesting strong niche processes (Grupe, 2014;Levin et al, 2017).…”
Section: Seeps As a Contrast To Ventsmentioning
confidence: 99%
“…important habitat for seep organisms (Marlow et al, 2014a,b;Case et al, 2015;Levin et al, 2015;Pasulka et al, 2016). Within each seep, folliculinids were observed living on a variety of these types of hard substrates (Figure 3).…”
Section: Discussion Distribution and Substrate Variability Of Seep-asmentioning
confidence: 99%
“…The Costa Rican margin exhibits strong vertical hydrographic gradients (Levin et al, ). Temperature ranges from 9.5 to 2.7°C at 400–1,800 m depth, bottom‐water O 2 concentration ranges from 0.04 to 1.6 ml/L, and pH ranges from 7.7 to 7.8 (Levin et al, ). The output of methane at Mound 12 is 15.5–52.5 × 10 3 mol year −1 , lower than that reported in other seas such as the Norwegian and the Mediterranean (Burkett, ).…”
Section: Methodsmentioning
confidence: 99%